Identification of Functional Limitations and Discharge Destination in Patients With COVID-19 - Roberts, Pamela; Wertheimer, Jeffrey; Park, Eunice; Nuño, Miriam; Riggs, Richard (Archives of physical medicine and rehabilitation, 2021)
The objectives of this study were to identify functional limitations in patients with coronavirus 2019 (COVID-19) admitted to acute care hospitals; to evaluate functional limitations by demographic, medical, and encounter characteristics; and to examine functional limitations in relation to discharge destination. and Setting:This is a cross-sectional, retrospective study of adult patients with COVID-19 who were discharged from 2 different types of hospitals (academic medical center and a community hospital) within 1 health care system from January 1 to April 30, 2020. Patients were identified from the Cedars-Sinai COVID-19 data registry who had a new-onset positive test for severe acute respiratory syndrome coronavirus 2. A total of 273 patients were identified, which included 230 patients who were discharged alive and 43 patients who died and were excluded from the study sample. Not applicable. Functional limitations in patients with COVID-19 in acute care hospitals and the predictors for discharge disposition. A total of 230 records were analyzed including demographic, encounter, medical, and functional variables. In a propensity score-matched cohort based on age and comorbidity, 88.2% had functional physical health deficits, 72.5% had functional mental health deficits, and 17.6% experienced sensory deficits. In the matched cohort, individuals discharged to an institution experienced greater physical (62.7% vs 25.5%, P<.001) and mental health (49.0% vs 23.5%, P=.006) deficits than patients discharged home. Marital status (odds ratio, 3.17; P=.011) and physical function deficits (odds ratio, 3.63; P=.025) were associated with an increase odds ratio of discharge to an institution. This research highlights that functional status is a strong predictor for discharge destination to an institution for patients with COVID-19. Patients who were older, in the acute care hospital longer, and with comorbidities were more likely to be discharged to an institution. Rehabilitation is a significant aspect of the health care system for these vulnerable patients. The challenges of adjusting the role of rehabilitation providers and systems during the pandemic needs further exploration. Moreover, additional research is needed to look more closely at the many facets and timing of functional status needs, to shed light in use of interdisciplinary rehabilitation services, and to guide providers and health care systems in facilitating optimal recovery and patient outcomes.